AUTOPSY-BASED STUDY FOR DETERMINATION AND EVALUATION OF AGE ESTIMATION THROUGH MACROSCOPIC EXAMINATION OF CRANIAL SUTURE CLOSURE BY ECTOCRANIAL METHOD AT MORTUARY COMPLEX OF SAURASHTRA REGION - RR, Bhabhor; Pandey , AR; Yadav, MS; Parmar , AP (Journal of Forensic Medicine and Toxicology, 2024)
Introduction: The lack of existing data pertaining to the Bhavnagar region, coupled with the inability to extrapolate findings from prior investigations, prompted the initiation of the present study. The primary objectives of this research were to elucidate the temporal progression of suture closure, ascertain sexual dimorphism, and evaluate the accuracy of age determination methods specific to the Bhavnagar region Materials and Methodology: A total of 100 cases of >20 years of age brought for medicolegal autopsy were analyzed. The coronal, sagittal, and lambdoid sutures were studied ectocranially. The degree of obliteration of sutures was scored ectocranially. Data were analyzed using Epi-info7 Software. Descriptive statistics were evaluated for continuous data, and categorical data were presented by frequency and percentages. An independent t-test was applied to find out the mean difference between the right and left sides of suture closure for ectocranial surfaces. Result: Regarding the chronology of suture closure, the present study found some variations compared to previous research. Notably, in the Sagittal suture, the anterior 1/ 3rd segment closed earlier in males, potentially due to lapsed union. Similarly, in the Coronal suture, the C1 segment closed first, followed by C2 and C3 in both genders. For the Lambdoid suture, L3 closed earlier than L2 and L1 in females, while L1 closed first in males. Conclusion: The present research highlights variations in gender and surface-based closure patterns. The erratic nature of suture obliteration necessitates caution when using it as the sole method for age estimation in forensic contexts.
Keywords: Ectocranial; cranial suture; Sagittal; Coronal; lambdoid.